How digital transformation improves corporate environmental management: A review and research agenda - Xia, Jiahui; Wu, Zhanchi; Chen, Binhai (Frontiers in Environmental Science, 2022)
Digital technologies offer opportunities and challenges for corporate environmental management (CEM). In this paper, we provide an overview of the literature on the relationship between digital transformation (DT) and CEM using a systematic review approach in the Antecedents, Decisions, and Outcomes (ADO) format. We review 181 papers published in almost 30 years from 1997 to 2022 and identify studies and areas where DT has impacted on CEM. We find that the literature examining the DT-CEM relationship has surged since 2019 and is concentrated in areas such as green sustainable science technology and environmental sciences. Further, we analyze the economic consequences of DT, the drivers of CEM, and the mechanisms of DT on CEM. Based on the literature analysis, we find that there is still a large gap in the literature studying the mediators and moderators of the DT-CEM relationship. Further, we find that firms with DT have better responsiveness and improved CEM by using digital resources to accurately capture the demands of different stakeholders on the environment. Finally, we provide a research framework and possible research directions, and propose corresponding management insights and policy recommendations.